Fewer accidents, more deaths. Agricultural mechanization in Brazilian sugarcane plantations and its effects on workers from 2012 to 2020 - Lima, José Rodolfo Tenório; Rumin, Cassiano Ricardo (Saúde e Sociedade, 2024)
The expansion of the use of machines in the field has promoted changes in the world of sugarcane work. Faced with this scenario, the question arises: How do work accidents and deaths behave in the mechanized reality of Brazilian sugarcane plantations? Predominantly quantitative, the research that supports this text uses secondary data collected from the Smartlab Platform and official government databases, linked to the formal labor market (RAIS). The results indicate that the set of agricultural activities (manual and mechanized) experienced a decrease in the incidence of work accidents, but did not show a reduction in the rate of work-related deaths. As a result, lethality increased in the period, demonstrating the preservation of the overexploitation of workers. This text is expected to shed light on the consequences generated by the agricultural mechanization process regarding the health and safety of sugarcane workers.